2013
DOI: 10.1007/s10729-013-9254-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach for the location of hand sanitizer dispensers in hospitals

Abstract: Compliance with hand hygiene practices is directly affected by the accessibility and availability of cleaning agents. Nevertheless, the decision of where to locate these dispensers is often not explicitly or fully addressed in the literature. In this paper, we study the problem of selecting the locations to install alcohol-based hand sanitizer dispensers throughout a hospital unit as an indirect approach to maximize compliance with hand hygiene practices. We investigate the relevant criteria in selecting dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…We used the metrics proposed by Cure et al 29 to evaluate the locations of sanitizer dispensers. The authors proposed 2 metrics: a usability score to evaluate individual locations within a room and a standardization score to complement the usability score at the unit level.…”
Section: Evaluation Of Dispenser Locationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the metrics proposed by Cure et al 29 to evaluate the locations of sanitizer dispensers. The authors proposed 2 metrics: a usability score to evaluate individual locations within a room and a standardization score to complement the usability score at the unit level.…”
Section: Evaluation Of Dispenser Locationsmentioning
confidence: 99%
“…It is suggested to make P k˛K u k ¼ 1 for ease of interpretation. Further suggestions to determine the weights of each characteristic are provided in Cure et al 29 Because hand hygiene data are usually collected by hospital patient care units, the individual room usability scores were used to calculate an average usability of a patient care unit as follows:…”
Section: Usability Scorementioning
confidence: 99%
See 2 more Smart Citations
“…The main components of the campaign comprised training, distribution of posters and provision of materials encouraging patients and relatives to clean their hands [15]. Furthermore, the campaign focused on improving environmental barriers, as recent studies have confirmed that HH compliance can be affected by the accessibility of sanitizing products [16,17].…”
Section: Introductionmentioning
confidence: 99%